1996
DOI: 10.1172/jci118470
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage and activation of pro-macrophage-stimulating protein by resident peritoneal macrophage membrane proteases.

Abstract: Macrophage stimulating protein (MSP), which is secreted as biologically inactive pro-MSP, is activated to MSP by cleavage at a single peptide bond. Our objectives were to determine the form of MSP in circulating blood and to study proteolytic activation of pro-MSP by its target cell. Western blot of immunoaffinity-purified serum MSP showed that all the protein was pro-MSP, without detectable MSP. The circulating form of the protein is therefore pro-MSP, and conversion to MSP does not occur when blood is shed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 32 publications
1
80
0
Order By: Relevance
“…Previous studies have identified a cell-surface, trypsin-fold serine protease activity on macrophages that activates MSP-1, potentiating MSP-1 binding to RON and subsequent macrophage activation (18-20). (Table 1), and (iii) MT-SP1 and RON are coexpressed in both peritoneal macrophages and cancer tissues, consistent with previous observations that MSP-1 is activated at the surface of cells that respond to MSP-1 (20). Activation of MSP-1 is the result of proteolysis C-terminal to R 483 (21).…”
Section: Mt-sp1 Is Present On the Cell Surface Of Peritoneal Macrophasupporting
confidence: 90%
“…Previous studies have identified a cell-surface, trypsin-fold serine protease activity on macrophages that activates MSP-1, potentiating MSP-1 binding to RON and subsequent macrophage activation (18-20). (Table 1), and (iii) MT-SP1 and RON are coexpressed in both peritoneal macrophages and cancer tissues, consistent with previous observations that MSP-1 is activated at the surface of cells that respond to MSP-1 (20). Activation of MSP-1 is the result of proteolysis C-terminal to R 483 (21).…”
Section: Mt-sp1 Is Present On the Cell Surface Of Peritoneal Macrophasupporting
confidence: 90%
“…Several aspects of MSP activation and signaling make it an attractive functional candidate for IBD. First, proteolytic activation of MSP have been proposed to occur in areas of active inflammation through cell-surface proteases located on macrophages (38), (39). Second, while MSP was originally identified as a protein that could elicit macrophage chemotaxis and activation, signaling though the MSP/MST1R has recently been shown to inhibit LPS or cytokine mediated production of inflammatory mediators (such as NO, COX2, PGE2 and IL-12p40) by macrophages, through the inhibition of NfkB signaling (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…MSP is secreted as a biologically inactive single chain precursor (pro-MSP) by the liver, and can be activated through proteolytic cleavage by serine proteases in areas of blood coagulation and active inflammation (38). Although the specific activating protease is unknown, a role for macrophage cell-surface proteases has been suggested from in vitro studies with cultured peritoneal macrophages and isolated macrophage membranes (39). MSP is the only known ligand for the MST1R, also known as RON receptor, a disulphide-linked heterodimer composed of an extracellular α chain and a transmembrane β chain with intrinsic kinase activity, expressed predominantly on tissue resident (differentiated) macrophages and epithelial cells (40).…”
Section: The Associated R689c Variant and Mst1 Functionmentioning
confidence: 99%
“…The level is not changed in the course of an acute phase reaction (21). To act on target cells in extravascular sites, pro-MSP must diffuse into tissues and be proteolytically cleaved to the biologically active disulfide-linked ␣␤ chain heterodimer (22). The EC 50 for the action of the MSP heterodimer on macrophages is 0.25 nM (1).…”
Section: Macrophage Stimulating Protein (Msp)mentioning
confidence: 99%
“…Several such proteases of the coagulation system, including factors XIa and XIIa and serum kallikrein cleave pro-MSP to active MSP in vitro (23). However, cleavage is minimal when blood clots, indicating that pro-MSP is not a preferred substrate for these enzymes (22). We have described two pro-MSP convertase activities in extravascular sites, one in wound fluid exudates (20) and the other associated with murine resident peritoneal macrophages (22).…”
Section: Macrophage Stimulating Protein (Msp)mentioning
confidence: 99%